Migraine with aura is associated with impaired colour vision: Results from the cross-sectional German DMKG headache study. (May 2015) - Jürgens, TP; Berger, K; Straube, A; Khil, L
Background: Hypersensitivity to light, noise and odour are pivotal clinical characteristics of migraine associated with enhanced cortical excitability and dysfunctional habituation. However, little is known about the integrity of basic sensory functioning in migraine on a population-based level. Methods: A total of 129 participants with migraine (105 without aura, MwoA, 24 with aura, MA) and 522 healthy controls without headache 12 months prior to baseline were included from a sample of the DMKG study and underwent standardised clinical sensory testing of smell, taste, hearing and vision. Results: After adjustment for age, sex, smoking status and history of head injuries, the chance of impaired colour perception was significantly higher in MA compared to controls (odds ratio, OR = 3.20; 95% CI = 1.20–8.53) and MwoA (OR = 3.62; 95% CI = 1.31–9.97). Compared to MwoA, MA also had an increased chance of smell (OR = 3.20; 95% CI = 0.98–10.42) and taste (OR = 2.58; 95% CI = 0.90–7.40) impairment. Conclusions: In this cross-sectional, population-based study on sensory functioning in migraine participants, colour vision was impaired interictally in MA compared to MwoA and controls.